INVESTIGATION OF THE STRENGTH AND DUTNESS OF REINFORCED CONCRETE BEAMS WITH GLASS COMPOSITE REINFORCEMENTS - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdugоfurovich; Mirzababaeva Sakhiba Mirzaakbarovna; Solijonov is the son of Foziljan Sadiqjan (Journals Park Publishing, 2022)
This article describes the analysis of the results of the research conducted on the study of the work of composite reinforced elements, which are widely used in the restoration of concrete structures in the buildings and structures currently being built in the Republic of Uzbekistan and in foreign countries.
Keywords: composite, basalt, concrete, flexibility, strength, messura, polymer.